A content analysis on the image of the female in male-oriented advertisements - Aguilar, Ilene
In every society, every person has to act out a certain role which is expected from him/her by the very society that he/she is in. The person then internalizes these expectations and acts accordingly. However, as time grows older, these expectations also experience some changes. These changes may vary in the speed of their development according to the society. For example, Western societies change more quickly than those of the East. They experiences more changes at a shorter period of time. Some of these changes occur in the East although it may take a longer time. One of these changes is the role of women in society. The women of today's generation have greater experiences open to them than their mothers and grandmothers. In terms of occupation, there are more fields open for her which is not just limited to the male population. In terms of success, she is not just limited to being a housewife and may even strive for the same kind of success which men have strived for. However, even in today's generation, stereotypes still exist. Some of them may exist in the minds of the people themselves while others exist somewhere else. One of these "somewhere else" is the mass media. Mass media may change or reinforce stereotypes and other images. This research was done in order to study the images of the women in male-oriented advertisement. This was done by analyzing twenty-four male-oriented television advertisements which were shown during December 1990. Several variable were studies to find out the over-all image of the women in such advertisements. The end of the study shows that the over-all image of the female was that she was seen as primarily an object of desire. She was slim and sexy and had no defined personality. She was used in the advertisement to support the male lead character/s to whom the advertisement was centered on. The women were not seen as being equal to the men. The researcher also found out that most of the male-oriented advertisements which featured women in such an image were those which targeted the lower income bracketts. The similar types of product like the different brands of alcoholic beverages, which catered to the upper class tended to show women as being equal to the male.